State anxiety and visual attention: The role of the quiet eye period in aiming to a far target - Behan, M.; Wilson, M. (Journal of Sports Sciences, 2008)
In this study, we examined how individuals controlled their gaze behaviour during execution of a far aiming task and whether the functional relationship between perception and action was disrupted by increased anxiety. Twenty participants were trained on a simulated archery task, using a joystick to aim and shoot arrows at the target, and then competed in two counterbalanced experimental conditions designed to manipulate the anxiety they experienced. The specific gaze behaviour measured was the duration of the quiet eye period. As predicted, accuracy was affected by the duration of the quiet eye period, with longer quiet eye periods being associated with better performance. The manipulation of anxiety resulted in reductions in the duration of quiet eye. Our results show that the quiet eye period is sensitive to increases in anxiety and may be a useful index of the efficiency of visual orientation in aiming tasks.